Nanotechnology enabled in situ sensors for monitoring health - Webster, Thomas J. 1971- (Springer, 2011)
Until recently, there has been little research into how to use nanotechnology and sensors in health monitoring. Nanotechnology Enabled In Situ Sensors for Monitoring Health is written to coalesce research efforts to design sensors based on nanotechnology that can be placed into the body to monitor health. Nanotechnology is being used at an unprecedented pace to both diagnose and treat diseases, rather than conventional approaches which diagnose and treat diseases in a different manner. Drawing upon the collective knowledge of renowned experts, Thomas Webster has assembled a wide-ranging treatise that includes: Nanotechnology for cancer sensing and treatment Monitoring tissue healing through nano sensors Monitoring inflammation and infection via implanted nano sensors DNA based nanotechnology biosensors for surgical diagnosis Carbon nanotube based orthopedic implant sensors Nanotechnology Enabled In Situ Sensors for Monitoring Health is a must-have for medical researchers, biomedical engineers and surgeons seeking a comprehensive overview of this important subject and examples of how In Situ sensors are being used in the diagnosis and monitoring diseases such as cancer, diabetes, and orthopedic problems.